PRETENSION OF THE QUDWAH METHOD: ISLAMIC SCHOOL INITIATIVE IMPROVES STUDENTS' INTERPERSONAL INTELLIGENCE MUHAMMAD QUTHB'S PERSPECTIVE - Munif, Muhammad; Qodriyah, Khodijatul; Fachri, Moh; Widat, Faizatul; Maknun, Irzat Jauharul (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
The aim of this research was a strong and advanced step from the qudwah method as the main initiative of Nurul Khalil Tenggarang Bondowoso Islamic High School in improving the interpersonal intelligence of students from Muhammad Qutb's perspective. This research used a qualitative approach with a field study type of research. Data collection techniques for this research were non-participant observation, semi-structured in-depth interviews with 4 informants, namely the Principal, Deputy Head of Curriculum, Deputy Head of Student Affairs, and 2 teachers, and documentation. The collected data was analyzed using the analytical model from Miles, Huberman, and Saldana with data condensation activities, data presentation, and final verification or drawing conclusions. The validity of the data was taken from the triangulation process of sources and techniques. The processes of the qudwah method that have been implemented by Nurul Khalil Islamic High School have been proven to increase students' interpersonal intelligence. The qudwah method was carried out through three main activities, namely qudwah qauliyyah, qudwah fi'liyyah, and qudwah syahsiyyah. This intelligence can be seen from the attitude of students who have the ability to speak verbally with other people, are able to adapt well in various situations, and are very skilled at reading the emotions of the people around them.